The redesign of blue- and white-collar work triggered by digitalization: collar matters. (March 2022) - Waschull, S.; Bokhorst, J.A.C.; Wortmann, J.C.; Molleman, E.
Highlights: Digitalization concurrently impacts blue- and white-collar work. Results show simplification for blue-collar work, enrichment for white-collar work. Effects depend on when and to what extent human factors are considered. System designers are motivated to craft their own tasks into attractive jobs. Organizations should include desired employee performance in their goal formulation. Abstract: The implementation of digital technologies in the context of Industry 4.0 radically changes methods of production and thereby the jobs of blue-collar workers. Although the work design effects of digitalization on the operator 4.0 have been explored in the existing literature, less is known about the simultaneous effects on white-collar work and the underlying (re)design process of human work including the factors that shape this process. To address this gap, we performed an in-depth industrial case study of an organization in the process of digitalization. Our findings confirm the concurrent impact of digitalization on blue- and white-collar work and suggest that its human implications highly depend on the extent to which, and at what moment, human factors are considered during the design and implementation process. Where work design knowledge lacked, the motivation of system designers turned out to be an important individual factor to realize favorable work design outcomes. At the organizational level, results show the importance of early involvement of system users and incorporating social performance indicators in addition to operational performance indicators in the statement of project goals. Our findings provide important empirical input for the further development of human-centric models and theories that integrate the challenges and opportunities for blue- and white-collar workers that are emerging when adopting digital technologies.